Language, thought, and the brain - Glezerman, T. B. (Tatʹi͡ana Borisovna) (Cognition and language., 1999)
Drawing on a wide variety of modern and classical sources and multiple disciplines, this book presents hypothesizes about the relationship between human language and thought to brain specialization. The authors focus on aphasia-language disorder resulting from local brain damage and show that the clinical aspect represents not only loss of function of the damaged area, but also results from the interaction between damaged and intact areas of the brain.